Characterization and antimicrobial activity of fungal endophytes from Crocus caspius (Iridaceae). (August 2022) - Samadzadeh, Samira; Farzaneh, Mohsen; Shahsavari, Zeinab; Ebrahimi, Samad Nejad; Asadollahi, Mojtaba; Mirjalili, Mohammad Hossein
Abstract: Plant endophytes are known as one of the newest natural sources for producing specialized metabolites and novel antibiotics. In the present study, endophytic fungi isolated from the corms of Crocus caspius Fisch. & C.A.Mey. ex Hohen. (Iridaceae) were characterized for the first time. Six fungal endophytes were isolated and their antibacterial activity was studied against human pathogens including Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Enterococcus faecium (Clinical isolate), and Candida albicans ATCC 10231 by determination of the minimum inhibitory-minimum bactericidal concentration (MIC-MBC) assays. Thin-layer chromatography (TLC)-bioautography technique was applied to investigate the antifungal activity of the methanolic extracts of fungal endophytes against ochratoxin A-producing fungus, Aspergillus ochraceus Strain 168. Based on morphological and ITS1-5.8S-ITS2 sequencing analysis, isolated endophytes from the plant corms were identified as Xenoacremonium falcatus (SBU-1), Fusarium oxysporum (SBU-2), Cadophora luteo-olivacea (SBU-3), Phialocephala sp . (SBU-4) and Talaromyces purpureogenus (SBU-5 and SBU-6). The extracts of T. purpureogenus SBU-6 (MIC = 1 mg/ml) and Phialocephala sp . SBU-4 (MIC = 0.25 mg/ml) showed a considerable antibacterial activity against E. coli and S. aureus, respectively. The obtained extract from SBU-5 showed the highest antifungal activity (MIC = 4 mg/ml) against C. albicans . Furthermore, both SBU-2 and SBU-5 at a concentration of 16 mg/ml showed bactericidal and fungicidal effects against E. coli and C. albicans . The extracts of SBU-2, SBU-4, and SBU-5 showed significant antifungal activity against A. ochraceous . These findings could be interesting for further exploitation of these endophytes to produce antibiotics and biological fungicides. Graphical abstract: Image 1 Highlights: Endophytes are known as one of the newest natural sources of novel antibiotics. Endophytic fungi isolated from the corms of Crocus caspius were characterized. The fungal extracts showed a significant activity against Aspergillus ochraceous. 16 mg/ml of the fungal extracts showed bactericidal and fungicidal effects.